Otoritas Agama dan Negara dalam Perspektif Thomas Hobbes: Refleksi atas Realitas Politik Indonesia - Felix Riondi Sugar; Oktavianus Nuba Dua; Alfeus Alfian Nenat; Fidelis Alfiano Dasar; Michael Savio Marpa Koi Niron; Hironimus Naras; Fridolin De’e; Epi Pianus Gregorius Gadja Wora (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines the relationship between religious authority and the state in the context of Indonesian politics from the perspective of Thomas Hobbes. This article aims to analyze how religion functions not only as a belief system but also as a socio-political force that influences the dynamics of state power. The method employed is qualitative research using a literature review approach (library research), which examines Hobbes’s ideas in Leviathan and their relevance to the political reality of Indonesia. The findings indicate that religion plays a dual role: as a source of morality and ethics and simultaneously as a political instrument capable of influencing power structures. From Hobbes’s perspective, religion is understood as part of social control that can strengthen state order through a social contract. However, in Indonesian political practice, religion is often used as a tool for legitimizing power, which has the potential to cause polarization. This study concludes that the relationship between religion and the state in Indonesia is complex and cannot be absolutely separated; therefore, proportional management is required so that religion remains a source of ethics, not a tool for political conflict.